The Relative Contribution of Academic Variables in Predicting Confidence in Mathematics among University Students - Alnaimi, Izzeldeen Abdullah (Journal of Ecohumanism, 2024)
This study aims to investigate the relative contribution of academic variables in predicting confidence in mathematics among university students. The sample of the study consisted of (N=313) students, including (222 males and 91 females, with a mean age of 21.15 years SD = 1.84). To achieve the objectives of the research, Math Confidence Rating Scale (MCS) developed by (Hendy et al., 2014), and it was validated by Alnaimi et al. (2024) to the Arab context, and has adequate psychometric properties to be used as a short measure of Math confidence in Arabic. Results revealed that academic variables (GAT, High school GPA, University cumulative GPA and Math Grade) affected university students’ math confidence with a percentage of 15.6% based on the R square value, indicating that the combined academic variables accounted for 15.6% of the variance in math confidence. These findings suggest a substantial relationship between academic variables and math confidence. Of these academic variables, Math Grade makes the largest and statistically significant contribution (Beta= 0.388).